Conservation and management of Canada’s polar bears ( Ursus maritimus) in a changing Arctic 1 This review is part of the virtual symposium “Flagship Species – Flagship Problems” that deals with ecology, biodiversity and management issues, and climate impacts on species at risk and of Canadian importance, including the polar bear ( Ursus maritimus), Atlantic cod ( Gadus morhua), Piping Plover ( Charadrius melodus), and caribou ( Rangifer tarandus). - Peacock, E.; Derocher, A.E.; Thiemann, G.W.; Stirling, I. (Canadian Journal of Zoology, 2011)
Canada has an important responsibility for the research, conservation, and management of polar bears ( Ursus maritimus Phipps, 1774) because the majority of polar bears in the world occur within the nation’s borders. Two fundamental and recent changes for polar bears and their conservation have arisen: (1) the ongoing and projected further decline of sea-ice habitat as a result of climate change and (2) the implementation of aboriginal land claims and treaties in Canada’s North. Science has documented empirical links between productivity of polar bear population and sea-ice change. Predictive modeling based on these data has forecast significant declines in polar bear abundance and distribution of polar bears. With the signing of northern land claims and treaties, polar bear management in Canada has integrated local aboriginal participation, values, and knowledge. The interaction of scientific and local perspectives on polar bears as they relate to harvest, climate change, and declining habitat has recently caused controversy. Some conservation, management, and research decisions have been contentious because of gaps in scientific knowledge and the polarization and politicization of the roles of the various stakeholders. With these ecological and governance transitions, there is a need to re-focus and re-direct polar bear conservation in Canada.